Evidence that Parkinson's disease is partly an Autoimmune Disease - Tuhami, Yara Masoud (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Parkinson's disease is a neurodegenerative disorder that affects dopaminergic neurons; the symptoms are the result of the gradual degeneration of nerve cells in the portion of the midbrain that controls body movements. For degenerative diseases like Parkinson's, any insights into its development in the brain could be vitally important in coming up with new ways and approaches for treatment. Several studies have been made to better understand this disease but new series of researches are focusing on the underlying autoimmunity of the disease and weather it plays a role in its progression or not. For this reason, a new series of studies could form a key piece of the puzzle. They have found the first direct evidence that autoimmunity contributes to Parkinson's disease, by extension raising the prospect of manipulating the body's immune system to slow or even
Parkinson's disease (PD) is a progressive disorder of the nervous system that affects movement. It develops gradually, sometimes starting with a barely noticeable tremor in just one hand. However, while a tremor may be the most well known sign of Parkinson's disease, the disorder also commonly causes stiffness or slowing of movement.1 In Parkinson's disease, certain nerve cells (neurons) in the brain gradually break down or die. Many of the symptoms are due to a loss of neurons that produce a chemical messenger in your brain called dopamine. When dopamine levels decrease, it causes abnormal brain activity, leading to signs of Parkinson's disease.